Clinical predictors of radiographic manifestations in advanced mandibular medication-related osteonecrosis of the jaw: a retrospective study - Jiayi Chen; Yuxuan Wang; Zhigang Cai; Jingang An (BMC Oral Health, 2026)
Abstract Background Medication-related osteonecrosis of the jaw is a debilitating adverse effect of antiresorptive and antiangiogenic therapies. Imaging plays a critical role in detecting lesions, assessing disease stage, and guiding treatment. This study aimed to evaluate the distribution of radiographic features in advanced mandibular medication-related osteonecrosis of the jaw and to explore their associations with clinical characteristics. Methods This retrospective study included 186 patients diagnosed with stage 2 or 3 mandibular medication-related osteonecrosis of the jaw between January 2015 and May 2024. Clinical data and imaging findings from computed tomography and panoramic radiography were analyzed. Imaging features included periosteal reaction, lesion density (sclerotic, osteolytic, or mixed), and sequestrum formation. Clinical variables comprised demographic characteristics, primary disease, laboratory parameters, medication type and duration, treatment history, lesion location, and disease course. Data were analyzed using univariate tests (chi-square, Mann-Whitney U , and t -tests) followed by multivariate logistic regression to identify independent predictors of imaging manifestations. Results Among the cohort, 88.2% of patients were at stage 3. Osteolytic lesions were the most prevalent imaging type (66%), while periosteal reaction and sequestrum formation occurred in 44% and 27% of patients, respectively. Multivariate analysis revealed that patients with subnormal hemoglobin levels, malignant primary diseases, or lesions involving the mandibular ramus and angle were significantly more likely to exhibit periosteal reaction. Furthermore, a longer disease course was an independent predictor for both the transition from sclerotic to osteolytic (destructive) lesion patterns and the occurrence of sequestrum separation. The median time to sequestrum formation was 12 months. Conclusions Periosteal reaction, bone destruction, sclerosis, and sequestrum formation are principal imaging features of MRONJ. Periosteal reaction is associated with low hemoglobin levels, malignant disease, and mandibular angle and ramus involvement. Longer disease duration is associated with osteolytic patterns and sequestrum separation, whereas shorter duration is associated with sclerotic changes. Trial registration Not applicable.